Community based initiatives to mainstream climate change adaptation into disaster risk reduction: evidence from the Hunter Valley (Australia). Issue 1 (2nd January 2019) - Forino, Giuseppe; von Meding, Jason; Brewer, Graham
ABSTRACT: In Australia, local communities often enact Community-Based Initiatives (CBIs) to respond to climate change through Climate Change Adaptation (CCA). CBIs can also be integrated into the Disaster Risk Reduction (DRR) agenda. The paper explores the extent to which CBIs promote the mainstreaming of CCA into DRR. Primary data were obtained from interviews with representatives of CBIs and supporting organisations in three local governments of the Hunter Valley (New South Wales, Australia). Findings show that CBIs recognise the potential contribution of climate change in modifying the local hazard profile. CBIs mainstream CCA into DRR by following four approaches: environmental and social justice; sustainability and transition; ecosystem-based approach; and adaptive planning. Partnerships were identified both among CBIs and between CBIs and City Councils; however, conflicts between CBIs, City Councils and business actors emerged, and a lack of commitment by multi-level governments in responding to climate change was revealed. The findings show that CBIs consider CCA and DRR within a broad everyday context related to vulnerability and local development. But we argue that assigning responsibility for climate change issues to CBIs is not a panacea and should not be the only local climate change response. Instead, CBIs need to be included in a larger and long-term commitment by actors that possess access to resources, such as higher levels of government. The paper provides a local Australian perspective on the effectiveness of mainstreaming CCA into DRR and furthers the conversation for the benefit of other communities facing similar challenges.